W. J. Connell, The Revised Ordinances of the City of Omaha, Nebraska, Embracing All Ordinances of a General Nature in Force April 1, 1890, Together with the Charter for Metropolitan Cities, the Constitution of the United States and the Constitution of the State of Nebraska, at 344, § 10 (1890) - (:unkn) unknown (General Publisher, 1890)
Prohibited the carrying of a concealed pistol or revolver, colt, billy, slungshot, brass knuckles or knuckles of lead, dirk, dagger, or any knife resembling a Bowie knife, or any other dangerous or deadly weapon. Punishable by fine up to $100.
--
Keywords: CARRY - CONCEALED